2014
DOI: 10.1007/s00383-014-3600-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute chest syndrome after laparoscopic splenectomy in children with sickle cell disease: operative time dependent?

Abstract: ACS is an important complication following laparoscopic splenectomy in patients with SCD. The immediate post operative management, in the absence of predictive factors for ACS, should be carefully followed in a high dependency unit at least for 48 h for all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…In a recent retrospective study, Bonnard et al reported the incidence of ACS following a laparoscopic splenectomy to be 23%. 9 In the present study, the incidence of ACS was much lower (8%). Other serious postoperative complications include pancreatitis due to an injury to the tail of the pancreas during a laparoscopic splenectomy, with a reported incidence of up to 15%.…”
Section: 21contrasting
confidence: 53%
See 2 more Smart Citations
“…In a recent retrospective study, Bonnard et al reported the incidence of ACS following a laparoscopic splenectomy to be 23%. 9 In the present study, the incidence of ACS was much lower (8%). Other serious postoperative complications include pancreatitis due to an injury to the tail of the pancreas during a laparoscopic splenectomy, with a reported incidence of up to 15%.…”
Section: 21contrasting
confidence: 53%
“…ACS was diagnosed according to previously described criteria. 9 Indications for splenectomies alone in children with SCD included either hypersplenism or acute splenic sequestration. Hypersplenism was defined as splenic enlargement with one of the following conditions: anaemia (requiring a transfusion of packed red blood cells exceeding 250 mL/kg per year); thrombocytopaenia (indicated by a platelet count of ≤100,000/mm 3 ); and neutropaenia (indicated by a white blood cell count of ≤4,000/mm 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,22,25 An overall morbidity of 19/150 cases (12.7%) is reported with ACS accounting for 11/150 (7.3%) .This morbidity rate after splenectomy is similar to other reports traced in the world literature. 11,12,16,18…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications for both open and laparoscopic splenectomy include intraoperative and postoperative bleeding, incision infection, pancreatic leak, rupture of the diaphragm, subphrenic hematoma, rupture of the colon, portal or splenic vein thrombosis, splenic hematoma, postoperative fever, acute chest syndrome and pulmonary complications, particularly in SCD children 2,6,7,9,27,28 . In our study, only one case of intraoperative bleeding was converted to laparotomy (a conversion rate of 2%), and postoperative pneumonia in 31% of patients.…”
Section: 96% Conversion To Openmentioning
confidence: 99%